Gaya Kepemimpinan Kepala Sekolah dan Semangat Kerja Guru dalam Melaksanakan Tugas Jabatan di Sekolah Dasar - Bambang Budi Wiyono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Leadership Styles of Principals and Teachers' Working Ethos at Elementary School. The purpose of the study was to examine the effect of principals' leadership styles on teachers' enthusiasm in carrying out their professional tasks. Sixty four principals and 256 teachers of public elementary schools in Bantul, Jogjakarta, were taken by cluster purposive sampling. The data were collected through questionnaires, interview, and documentary studies. The results showed that teachers' working ethos was higher when they were led by principals using the integrated-or the people-oriented leadership style than by those using the task-or the impoverished leadership style. There was no interactional effect of the leadership styles and school quality on teachers' enthusiasm.